2015
DOI: 10.1111/tid.12402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HMG‐CoA reductase inhibitors on the incidence of polyomavirus‐associated nephropathy in renal transplant recipients with human BK polyomavirus viremia

Abstract: Introduction Up to 20% of renal transplant recipients (RTR) will develop human BK polyomavirus (BKPyV) viremia. BKPyV viremia is a pre-requisite of polyomavirus-associated nephropathy (PyVAN). Risk of BKPyV infections increases with immunosuppression. Currently, the only effective therapy against PyVAN is reductions in immunosuppression; but this may increase the risk of rejection. In vitro data have shown that pravastatin dramatically decreased caveolin-1 expression in human renal proximal tubular epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Second, our lab showed that SV40 trafficking is cell type-dependent (Bennett et al, 2013). Third, an in vitro study showed that the 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitor Pravastatin, which inhibits cholesterol synthesis, prevents BKPyV infection by depleting caveolin 1 protein in RPTE cells (Moriyama et al, 2008); however, a clinical trial using Pravastatin failed to protect patients from PVAN at the maximum effective dose (Gabardi et al, 2015). Lastly, a study focused on BKPyV trafficking in human kidney cells supported the previous animal model that BKPyV entry is caveolin-dependent (Moriyama et al, 2007); however, we were unable to reproduce the results of Moriyama et al by exactly following their reported protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our lab showed that SV40 trafficking is cell type-dependent (Bennett et al, 2013). Third, an in vitro study showed that the 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitor Pravastatin, which inhibits cholesterol synthesis, prevents BKPyV infection by depleting caveolin 1 protein in RPTE cells (Moriyama et al, 2008); however, a clinical trial using Pravastatin failed to protect patients from PVAN at the maximum effective dose (Gabardi et al, 2015). Lastly, a study focused on BKPyV trafficking in human kidney cells supported the previous animal model that BKPyV entry is caveolin-dependent (Moriyama et al, 2007); however, we were unable to reproduce the results of Moriyama et al by exactly following their reported protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of in vitro findings suggesting that statins prevent caveolar-dependent entry of BK virus (BKV), a Polyomaviridae member, into proximal tubular epithelial cells [ 23 ], and clinical studies reporting that statins reduced proteinuria and the progression of kidney disease by improving renal function [ 135 ], a retrospective study was conducted in renal transplant recipients with documented BKV viremia taking or not statins to treat hyperlipidaemia. The study failed to demonstrate a beneficial effect of statins, at least at doses maximized for cholesterol lowering, and the authors highlighted the need to perform studies other than Randomized Clinical Trials (RCT) to identify the statins’ doses able to counteract the virus progression [ 136 ].…”
Section: Pros and Cons Of Statins And Mevalonate Pathway Inhibitors In Viral Infectionsmentioning
confidence: 99%
“…HMG-CoA reductase inhibitors are another class of drugs that has been tried unsuccessfully for the treatment of BKV infection. After the original in vitro observation that pravastatin blocks BKV cellular entry[ 449 ], a retrospective multicenter study failed to show any effect of statin doses that maximize their cholesterol-lowering effect on BK viruria or the development of BKN in renal transplant recipients[ 479 ]. Intravenous ( i.v .)…”
Section: Part C Treatment Of Bkv Infection: Diseases Caused By Other mentioning
confidence: 99%